2011
DOI: 10.1016/j.vetmic.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of West Nile virus circulation in Portugal

Abstract: International audienceThe circulation of West Nile virus in Portugal was assessed by serological surveys conducted during 2004-2010 in horses and birds. The detection of WNV antibodies in both species in all the years covered by the study as well as the presence of anti-WNV IgM in symptomatic horses that had not traveled outside the country, support the notion that WNV circulates in Portugal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
1
16
1
1
Order By: Relevance
“…Recent scientific reports of increasing flaviviruses activity during the last decade in the Mediterranean basin underline the importance of passive surveillance of horses in the European Union (e.g. Barros et al, 2011;Chaskopoulou et al, 2011;Garc ıa-Bocanegra et al, 2011a;Spissu et al, 2013). However, because of the antigenic similarities between flaviviruses like Usutu virus Japanese encephalitis virus among others, each clinical suspected case must be confirmed by the use of SNT reaction against WNV (Shi and Wong, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent scientific reports of increasing flaviviruses activity during the last decade in the Mediterranean basin underline the importance of passive surveillance of horses in the European Union (e.g. Barros et al, 2011;Chaskopoulou et al, 2011;Garc ıa-Bocanegra et al, 2011a;Spissu et al, 2013). However, because of the antigenic similarities between flaviviruses like Usutu virus Japanese encephalitis virus among others, each clinical suspected case must be confirmed by the use of SNT reaction against WNV (Shi and Wong, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…While overwintering mechanisms cannot be ruled out (Sotelo et al., ), modelling suggests that these mechanisms are not sufficient to explain the observed European WNF outbreaks (Durand et al., ). Regular European outbreaks of WNF in horses and/or humans have been reported in France [outbreaks in the Camargue region in 2000, 2003, 2004 (Murgue et al., ; Leblond et al., )], Romania [in 1996 and 2010, and several cases in 1997 and 1998 (Tsai et al., ; Cernescu et al., ; Rabel et al., )], Italy [in 1998 and 2008–2009 (Cantile et al., ; Calistri et al., ; Monaco et al., )], Russia [in 1999 and 2010 (Platonov et al., ; Rabel et al., )], Hungary [in 2008 and 2010 (Kutasi et al., ; Rabel et al., )], several cases since 1997 in the Czech Republic (Rabel et al., ), Greece [in 2010 and 2012 (Anonymous, ; Rabel et al., ; Cnops et al., )], Spain [in 2010, 2011, 2012 (García‐Bocanegra et al., ; Ministerio de Agricultura, Alimentación y Medio Ambiente, )], and some cases of WNF have been reported in Portugal (Barros et al., ). In addition, although in absence of disease, increased titres of antibodies have been encountered from human intravenous plasma preparations in Germany and Austria (Rabel et al., ), and seropositive horses have been recently identified in Croatia (Madic et al., ; Barbić et al., ) and Serbia (Lupulovic et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, the virus reappeared in association with human cases of neurological disease in 2008 [11,12]. In addition, different seropositivity rates have been reported for horses, humans and birds in Spain [13,14] and Portugal [15,16], with the first clinical cases of WNV-related disease being reported in Spain for horses and humans in 2010 [17]. Evidence of WNV circulation among birds has been reported in the UK since 2003, and in 2006 the use of sentinel chickens corroborated the epidemiological data about WNV in the UK by demonstrating actual seroconversion [18,19].…”
Section: Epidemiology Of Wnv In Eu Member Countries and Neighbouring mentioning
confidence: 99%
“…In some instances in Europe, equine cases have been observed without substantial human disease being reported, such as in Tuscany, Italy (1998) (Autorino et al, 2002) and Camargue (Pantheir et al, 1966), France (2000); however, in North America equine and human cases have demonstrated similar incidence patterns, both before and after widespread vaccination of horses (Ward and Scheurmann, 2008). Since 2010, WNV infections among horses repeatedly were reported in the Mediterranean basin and other European countries, namely in Bulgaria, Croatia, Greece, Italy, Macedonia, Morocco, Portugal, Romania and Spain (Barros et al, 2011; Garcia-Bocanegra et al, 2011; OIE, 2012). The aforementioned WNV equine epizootics before 2007 were associated with lineage 1 viruses.…”
Section: Epidemiology In Horsesmentioning
confidence: 99%